Selection of polymeric materials : how to select design properties from different standards - Campo, E. Alfredo (William Andrew, 2008)
Today engineers, designers, buyers and all those who have to work with plastics face a dilemma: the proliferation of test methods by which plastic properties are measured. The property data measured by these test methods are not identical and sometimes have large differences. How are engineers, designers, and buyers to decide the type and resin grade and their property data? Which are the valid test methods? The right plastic property data are the difference between success and failure of a design, thus making the property selection process critical. There are over 26,000 different grades of polymers and millions of parts and applications, further adding to the difficulty of the selection process. For the first time a single resource provides a simple and efficient approach to this highly complex and time consuming task. Selection of Polymeric Materials steers engineers and designers onto the right path to selecting the appropriate values for each plastic property. A large amount of property information is provided to teach and assist the plastic part designer and others in selecting the right resin and properties for an application. Various standards including ASTM, ISO, UL, and British Specifications are discussed to help the readers in making sound decisions."
Keywords: Polymers.; Polymeric composites.; Polymers -- Standards.; Polymers -- Electric properties.; Polymers -- Mechanical properties.; Polymers -- Thermal properties.; Polymers -- Deterioration.; elektronické knihy; electronic books